Analisis Penggunaan Hedges pada Buku Teks Bahasa Inggris Kelas 11 - Efendi, Musa; Lestari, Titis Yekti; Utami, Irma Fajar Tri; Odik, Harman (Universitas Negeri Surabaya, 2024)
This study investigates the use of hedging maxim of quality and quantity in the Bahasa Inggris Kelas XI Kurikulum 13 textbook. The research method employed is descriptive qualitative, where researchers analyze the contents of the book to identify hedge maxims. The findings reveal the presence of hedges in the maxim of quality and quantity throughout the book. Hedges of maxim quality are used by speakers who are unsure about the information they convey, while hedges of maxim quantity are used by speakers who acknowledge limited information on a topic. The finding results there are 14 types of hedging maxims of quality and 11 types of hedging maxims of quantity in the Bahasa Inggris Kelas XI Kurikulum 13 textbook. The use of hedges in this textbook aligns with Grice's maxims of conversation, specifically the maxims of quality and quantity. This analysis can help educators understand how linguistic features are used in educational contexts to enhance the effectiveness of teaching materials.